Conservative Management of Chronic Internal Resorption With Concomitant Periapical Pathology Using Injectable Platelet-Rich Fibrin: A Review of Literature - Shilpa Shetty; Lida Mary Nidhin-Philip; Malasa H Pai; Supra Rathan-Karkera (Journal of Health and Allied Sciences NU, 2026)
Chronic internal resorption is a rare, progressive inflammatory condition characterized by the loss of dental hard tissue from within the root canal system. When associated with periapical pathology, the management becomes more complex. Tooth resorption can occur either internally (originating from the pulp) or externally (originating from the periodontium), and it can be classified as either normal or pathological. Internal resorption is relatively uncommon and poses challenges for both diagnosis and treatment. Typically asymptomatic, it is often discovered incidentally during routine radiographic examinations or may be indicated by a characteristic clinical sign known as a “pink spot” on the crown of the tooth. However, recent advances in biomaterials, particularly the use of injectable platelet-rich fibrin (I-PRF), have introduced a regenerative approach. Before the diagnosis of internal resorption can be made, it is necessary to rule out subepithelial external inflammatory root resorption or cervical resorption, which is progressive external root resorption of inflammatory origin that occurs immediately below the tooth’s epithelial attachment. The pink tooth is caused by the granulation tissue that is undermining the enamel. A structured literature search was performed using PubMed, Scopus, and Google Scholar, and relevant studies were qualitatively analysed. This research highlights the aetiology and pathophysiological mechanisms involved in internal root resorption.